2017
DOI: 10.1002/asia.201701170
|View full text |Cite
|
Sign up to set email alerts
|

Room‐temperature Synthesis of Amorphous Molybdenum Oxide Nanodots with Tunable Localized Surface Plasmon Resonances

Abstract: Two-dimensional (2D) semiconductors have recently emerged as a remarkable class of plasmonic alternative to conventional noble metals. However, tuning of their plasmonic resonances towards different wavelengths in the visible-light region with physical or chemical methods still remains challenging. In this work, we design a simple room-temperature chemical reaction route to synthesize amorphous molybdenum oxide (MoO ) nanodots that exhibit strong localized surface plasmon resonances (LSPR) in the visible and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…However, their applications in integrating optics devices have always been hampered by the high optical losses due to interband transitions, large real component of their dielectric constant, and fixed carrier density . In the past few years, the search of low‐loss and widely tunable plasmonic media has led to the development of diverse nonmetallic plasmonic nanocrystals, such as copper chalcogenides, transparent conducting oxides, and oxygen‐deficient metal oxides . These nonmetallic plasmonic materials exhibit enormous advantages in device performance, design flexibility, and property tunability.…”
Section: Introductionmentioning
confidence: 99%
“…However, their applications in integrating optics devices have always been hampered by the high optical losses due to interband transitions, large real component of their dielectric constant, and fixed carrier density . In the past few years, the search of low‐loss and widely tunable plasmonic media has led to the development of diverse nonmetallic plasmonic nanocrystals, such as copper chalcogenides, transparent conducting oxides, and oxygen‐deficient metal oxides . These nonmetallic plasmonic materials exhibit enormous advantages in device performance, design flexibility, and property tunability.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the corresponding SAED pattern of the H x MoO 3 quantum dots is shown in Figure d. The pattern of a typical halation without diffraction ring indicates its amorphous structure …”
mentioning
confidence: 97%
“…Compared with the XRD pattern of bulk MoO 3 , a weak and broad peak appears in the range of 20–30°, which is assigned to the orthorhombic phase of MoO 3 (JCPDs no. 05‐0508) . It means that the crystallinity of the sample is extremely poor, so it can be suggested that MoS 2 has been transferred into amorphous MoO 3 after the oxidization process.…”
mentioning
confidence: 99%
“…c) UV/Vis‐NIR diffuse reflectance spectra of the sample reduced in different solvent/water mixtures. Reprinted from reference . Copyright 2017 Wiley‐VCH.…”
Section: Amorphous Materials With Lsprmentioning
confidence: 58%
“…It is also possible to introduce vacancies to manipulate the carrier density in the semiconductor nanocrystals post‐synthetically. This method was studied in our recent work on amorphous MoO 3− x nanodots . We demonstrated that amorphous molybdenum oxide (MoO 3 ) nanodots could be obtained by means of a facile sonochemistry approach, and they exhibited strong LSPR absorption in the visible and NIR regions (Figure ).…”
Section: Amorphous Materials With Lsprmentioning
confidence: 99%